Tribotechnical properties of experimental hard alloys with modified cobalt binder - E. V. Fominov; C. G. Shuchev; M. M. Aliev (Advanced Engineering Research, 2022)
Introduction. This paper discusses tribomechanical characteristics of experimental hard alloys with a modified cobalt binder under friction without lubrication on hard-to-cut materials – stainless steel and titanium alloy. The research objective is to evaluate the process of friction interaction for each friction pair according to a number of parameters, and to determine the optimal combinations of “experimental hard alloy – structural material” on the basis of the established tribological indicators.Materials and Methods. Tribological tests of hard alloys were carried out using a cylinder-to-disc friction scheme for different sliding speeds and temperatures under constant load without the use of lubricants. Comparison of the friction interaction process was carried out by the frictional force, volumetric wear and roughness of the friction tracks on the counterbody. Stainless steel 12H18N9Т and titanium alloy ВТ3-1 were used as counterbody materials. The resistance of experimental compositions to the abrasive type of wear was determined through measuring the surface dynamic microhardness on a scanning nanohardness tester by analyzing the thickness of the scratches caused by the indenter.Results. According to the results of surface microindentation, the experimental alloys 2.22 (binder 5.65% Co + l.8% Mo + 0.6% Ti) and 2.23 (binder 5.1% Co + 2.7% Mo + 0.61 % Ti) are characterized by the highest microhardness. For these materials, the average scratch width at various forces was minimal. During tribological tests, the best frictional characteristics were recorded for stainless steel in combination with experimental alloy 2.22, and for the friction pair “titanium alloy VT3-1 — hard alloy 2.23”. The friction of this combination of materials was characterized by low friction coefficients with a low level of fluctuations, minimal wear of samples, and changes in the initial microrelief of their surfaces.Discussion and Conclusions. As a result of the research, the optimal friction pairs from the point of view of tribological interaction were established, specifically “titanium alloy VT3-1 — hard alloy 2.23” and “stainless steel 12X18N9T – hard alloy 2.22”. The frictional interaction for these combinations of materials is characterized by minimal volumetric wear, which will contribute to increasing the wear resistance of the tool in the areas of elastic contact on the front and rear surfaces.